2020
DOI: 10.1371/journal.pone.0231313
|View full text |Cite
|
Sign up to set email alerts
|

Is bad news on TV tickers good news? The effects of voiceover and visual elements in video on viewers’ assessment

Abstract: In our experiment, we tested how exposure to a mock televised news segment, with a systematically manipulated emotional valence of voiceover, images and TV tickers (in the updating format) impacts viewers' perception. Subjects (N = 603) watched specially prepared professional video material which portrayed the story of a candidate for local mayor. Following exposure to the video, subjects assessed the politician in terms of competence, sociability, and morality.Results showed that positive images improved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…The literature continues to show differing results on what kinds of messages work, however. With regard to images and visuals and their impacts on viewer perception, other studies have shown that positive images and additional, verbal information can have a corresponding positive impact on viewer perceptions of messages such as advertisements (Meade & Zhou, 2017) or political campaigns (Maj & Lewandowsky, 2020). When it comes to visuals and hurricanes, Rickard and colleagues (Rickard et al, 2017) noted that images of dramatic storm damage can increase awareness among those subjects who had not yet experienced a hurricane; however, some of the reactions/assessments of storm risk in those subjects could be extreme or over-the-top compared to the actual risk.…”
Section: Risk Perception and Messagingmentioning
confidence: 99%
“…The literature continues to show differing results on what kinds of messages work, however. With regard to images and visuals and their impacts on viewer perception, other studies have shown that positive images and additional, verbal information can have a corresponding positive impact on viewer perceptions of messages such as advertisements (Meade & Zhou, 2017) or political campaigns (Maj & Lewandowsky, 2020). When it comes to visuals and hurricanes, Rickard and colleagues (Rickard et al, 2017) noted that images of dramatic storm damage can increase awareness among those subjects who had not yet experienced a hurricane; however, some of the reactions/assessments of storm risk in those subjects could be extreme or over-the-top compared to the actual risk.…”
Section: Risk Perception and Messagingmentioning
confidence: 99%